Effect of nutritional status at dialysis intiation on patient survival - Kunihiro Yamagata; Shigeru Nakai; Ikuto Masakane; Norio Hanafusa; Kunitoshi Iseki; Yoshiharu Tsubakihara (The Korean Society of Nephrology, 2012)
Better nutritional status and early initiation of dialysis had been considered one of the most important methods for better prognosis of dialysis patients. In this study, we analyzed the effects of nutritional status, renal function at the start of renal replacement therapy (RRT), and co morbidity on 12-month survival of ESRD patients. The subjects in this study were 9695 new ESRD patients who started RRT in 2007 in Japan. The average age of the subjects was 67.5 years, 64.1% of the subjects were male, and 42.9% had diabetes. During the 12-month period after the start of RRT, 1546 patients died, and 35 patients received renal transplantation. Average estimated glomerular filtration rate (eGFR) at the initiation of dialysis was 6.52+ 4.20 mL/min/1.73 m2. Average serum albumin was significantly higher (P<0.001) in survivor (3.3+0.6 g/dl in survivor and 2.9+0.7 g/dl in expired patients) at the initiation of RRT. One-year odds ratio (OR) of mortality in patients with eGFR more than 4-6 ml/min/1.73 m2 was increased with increased eGFR at dialysis initiation, but OR was identical among the groups with eGFR less than 4 ml/min/1.73 m2. Not only patients with sufficient residual renal function at the initiation of dialysis, but also patients with low nutritional status at the initiation of dialysis showed poor survival.